Identification of ILK as a critical regulator of VEGFR3 signalling and lymphatic vascular growth. (5th December 2018) - Urner, Sofia; Planas‐Paz, Lara; Hilger, Laura Sophie; Henning, Carina; Branopolski, Anna; Kelly‐Goss, Molly; Stanczuk, Lukas; Pitter, Bettina; Montanez, Eloi; Peirce, Shayn M; Mäkinen, Taija; Lammert, Eckhard
Abstract: Vascular endothelial growth factor receptor‐3 (VEGFR3) signalling promotes lymphangiogenesis. While there are many reported mechanisms of VEGFR3 activation, there is little understanding of how VEGFR3 signalling is attenuated to prevent lymphatic vascular overgrowth and ensure proper lymph vessel development. Here, we show that endothelial cell‐specific depletion of integrin‐linked kinase (ILK) in mouse embryos hyper‐activates VEGFR3 signalling and leads to overgrowth of the jugular lymph sacs/primordial thoracic ducts, oedema and embryonic lethality. Lymphatic endothelial cell (LEC)‐specific deletion of Ilk in adult mice initiates lymphatic vascular expansion in different organs, including cornea, skin and myocardium. Knockdown of ILK in human LECs triggers VEGFR3 tyrosine phosphorylation and proliferation. ILK is further found to impede interactions between VEGFR3 and β1 integrin in vitro and in vivo, and endothelial cell‐specific deletion of an Itgb1 allele rescues the excessive lymphatic vascular growth observed upon ILK depletion. Finally, mechanical stimulation disrupts the assembly of ILK and β1 integrin, releasing the integrin to enable its interaction with VEGFR3. Our data suggest that ILK facilitates mechanically regulated VEGFR3 signalling via controlling its interaction with β1 integrin and thus ensures proper development of lymphatic vessels. Synopsis: Tight regulation of VEGFR3 signaling, which ensures proper lymph vessel development, has been studied mostly at the level of VEGFR3 activation. This study identifies integrin‐linked kinase (ILK) as mechanosensitive negative regulator of VEFGR3 signaling, which acts by perturbing the interaction between β1 integrin and VEGFR3. Endothelial cell‐specific ILK depletion in mouse embryos causes hyperactivation of VEGFR3 signaling, overgrowth of jugular lymph sac, oedema and embryonic lethality. Lymphatic endothelial cell (LEC)‐specific depletion of ILK in adult mice initiates lymphatic vascular expansion in multiple organs, including cornea and myocardium. ILK perturbs the interaction between VEGFR3 and β1 integrin in vitro and in vivo, thereby inhibiting VEGFR3 signaling. Mechanical stimulation of LECs disrupts the interaction between ILK and β1 intergin. Endothelial‐cell specific heterozygous deletion of the gene encoding β1 integrin rescues the lymphatic vascular phenotype observed upon ILK depletion in mouse embryos. Abstract : Lymphatic endothelial cell‐specific depletion of integrin‐linked kinase (ILK) in mice identifies it as mechanosensitive regulator of physiological lymph vessel expansion.